Theme session B - Spatial management, climate change,​ and biodiversity​​ ... - ICES (ASC 2022 - Theme session B, 2022)
ICES Annual Science Conference Book of abstracts for theme session B: Spatial management, climate change and biodiversity Conveners: Catarina Frazão Santos (Portugal), Andrew Kenny (UK), Tundi Agardy (USA) CM 11: Lyme Bay Offshore Mussel Farm – an OECM case study CM 29: Requirements and availability of prey for north-eastern pacific southern resident killer whales CM 35: Fine-scale oceanographic drivers of pelagic biomass around a tropical coral atoll within the Chagos Archipelago Marine Protected Area CM 40: Jointly modelling Atlantic bottlenose dolphin distributions and prey species: evidence of strong ties to drumming prey species and temperature CM 49: Can High-Seas Fisheries Closures Qualify as Other Effective Conservation Areas? CM 54: Deep-sea silver scabbardfish Lepidopus caudatus ecology, biology, and fisheries in the Azores CM 58: Developing a subseasonal forecasting tool to reduce fisheries bycatch in the Northeast US CM 96: Vulnerability Analysis of the Western Baltic Small-Scale Fishery CM 127: ...